Analisis Kualitas Pelayanan Angkutan Sampah UPT Pengelolaan Sampah di Kabupaten Bogor - Syaiful Anwar; Mujito Mujito (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to analyze the quality of waste transportation services provided by the Waste Management UPT in Bogor Regency, with a case study in Harapan Jaya Village. The research employed a descriptive quantitative approach using questionnaires distributed to 100 community respondents. The variables examined refer to the five service quality dimensions, namely tangibles, reliability, responsiveness, assurance, and empathy. The findings indicate that community perceptions of waste transportation services fall into the “fairly good” category, with an overall average score of 3.39. Specifically, the tangibles dimension scored 3.46 (fairly good), reliability 3.47 (fairly good), responsiveness 3.16 (fairly good but lowest), assurance 3.21 (fairly good), and empathy 3.63 (good, highest). These results suggest that waste transportation services have been running fairly well, though improvements are needed, particularly in responsiveness. The study’s findings are expected to provide input for the Bogor Regency Environmental Agency to enhance the effectiveness and quality of waste management services, as well as encourage greater community participation in maintaining environmental cleanliness.